Mesozoic to Cenozoic intracontinental deformation and dynamics of the North China Craton. (17th March 2013) - Li, S. Z.; Suo, Y. H.; Santosh, M.; Dai, L. M.; Liu, X.; Yu, S.; Zhao, S. J.; Jin, C.
Abstract : Since the Mesozoic, the North China Craton has been located at a triangular junction surrounded by subduction or collision zones. This craton thus marks the frontier of a super‐convergent regime. Within the super‐convergence tectonic domains, however, distinct extensional regimes operated in the Meso‐Cenozoic Bohai Bay Basin located at the eastern part of the North China Craton. In this synthesis, we focus on the intracontinental dynamics during the Mesozoic to Cenozoic in the North China Craton. Whereas the deep structures as revealed from tomographic studies show a remarkable difference between the Western and Eastern blocks of the North China Craton, the shallow setting in both regions is characterized by super‐convergence. We propose here that the tectonic scenario of the Bohai Bay Basin developed during the destruction of the North China Craton is largely characterized by Mesozoic extrusion and Cenozoic NW‐directed intracrustal extension with pull‐apart. The Cenozoic deep process is mainly a regional far‐field eastward upwelling of the asthenosphere beneath the western tectonic domain due to the India–Eurasia Plate collision accompanied by the eastward jump and rollback of the subducting Pacific Plate. The deep processes under the Bohai Bay Basin in the Mesozoic are local delamination and magma underplating. Our study highlights the contrasting structural and tectonic signature developed in the frontier of one of the largest super‐convergent systems on the globe. Copyright © 2013 John Wiley & Sons, Ltd.